2023
DOI: 10.3390/fluids8030085
|View full text |Cite
|
Sign up to set email alerts
|

Adjoint-Based High-Fidelity Concurrent Aerodynamic Design Optimization of Wind Turbine

Abstract: To evaluate novel turbine designs, the wind energy sector extensively depends on computational fluid dynamics (CFD). To use CFD in the design optimization process, where lower-fidelity approaches such as blade element momentum (BEM) are more popular, new tools to increase the accuracy must be developed as the latest wind turbines are larger and the aerodynamics and structural dynamics become more complex. In the present study, a new concurrent aerodynamic shape optimization approach towards multidisciplinary d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…As in our earlier research [47], we used the NREL Phase VI, which has just two blades, as the baseline geometry in this investigation. Regarding the aerodynamic component, the surface mesh as shown in Figure 5c is constructed in ICEM CFD, and the spherical volume mesh as shown in Figure 5a is created by extruding the structured surface mesh using the opensource mesh generator pyHyp [48].…”
Section: Baseline Geometry Configuration For Aerostructural Optimizationmentioning
confidence: 99%
“…As in our earlier research [47], we used the NREL Phase VI, which has just two blades, as the baseline geometry in this investigation. Regarding the aerodynamic component, the surface mesh as shown in Figure 5c is constructed in ICEM CFD, and the spherical volume mesh as shown in Figure 5a is created by extruding the structured surface mesh using the opensource mesh generator pyHyp [48].…”
Section: Baseline Geometry Configuration For Aerostructural Optimizationmentioning
confidence: 99%
“…It has been reported that gradient-based optimization can be an efficient tool for largescale optimization such as an aircraft's wing or a whole aircraft by considering a set of design variables in order to maximize the object performance [14,15]. Batay et al [16] studied the adjoint-based high-fidelity aerodynamic design optimization of a wind turbine by implementing the DAFoam tools. Koyuncuoglu and He [17] simultaneously optimize the wing shape and actuator parameters using high-fidelity computational fluid dynamics with adjoint optimization approach.…”
Section: Introductionmentioning
confidence: 99%